2006
DOI: 10.1186/1471-2180-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Induction of temperate cyanophage AS-1 by heavy metal – copper

Abstract: Background: It has been reported that some marine cyanophage are temperate and can be induced from a lysogenic phase to a lytic phase by different agents such as heavy metals. However, to date no significant reports have focused on the temperate nature of freshwater cyanophage/ cyanobacteria. Previous experiments with cyanophage AS-1 and cyanobacteria Anacystis nidulans have provided some evidence that AS-1 may have a lysogenic life cycle in addition to the characterized lytic cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…4 ; t test, P < 0.05). Previous studies have also shown that heavy-metal pollutants induce lytic bacteriophages in marine bacteria ( 21 , 22 ). The remarkable enrichment of phages caused by copper treatment suggested the multiplication of phages and lysis of their hosts.…”
Section: Resultsmentioning
confidence: 86%
“…4 ; t test, P < 0.05). Previous studies have also shown that heavy-metal pollutants induce lytic bacteriophages in marine bacteria ( 21 , 22 ). The remarkable enrichment of phages caused by copper treatment suggested the multiplication of phages and lysis of their hosts.…”
Section: Resultsmentioning
confidence: 86%
“…It is common place that both lytic and lysogenic strategies are present in complex environmental microbial communities [57], and lysogeny is thought to be favored under adverse conditions by enhancing both phage and host survival in soils [58]. Furthermore, phage cycles are rarely triggered spontaneously [59], as they often respond to external cues/stressors [57], including metal (e.g., Cu) [60]. One key molecular signal involved in phage-triggering is the host cell DNA repair mechanisms, so-called “SOS response” [61], which are activated upon DNA damage (e.g., caused by pollutants) [62].…”
Section: Resultsmentioning
confidence: 99%
“…to act as hosts within the samples. The understanding of cyanophage populations is important due to the fact that it can potentially be used as a CHAB control by reducing the amount of cyanobacteria in a biological rather than chemical methods that are currently in use [21]. In the future it may be prudent to employ more species-specific primers to identify the cyanobacteria and cyanophage populations.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanophages alter populations of cyanobacteria and can play a role in community composition, depending on the cyanophage types present. Given their ability to affect community structure, cyanophages have a critical role in reducing the frequency and strength of CHABs [20] [21]. The aim of this study is to rapidly detect and characterize the cyanobacteria and their phages of Barnegat Bay.…”
Section: Introductionmentioning
confidence: 99%